The Role of the Sharia Supervisory Board in Protecting Member Rights on Murabahah Financing Products - Via Regita; Irvan Iswandi (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
The Sharia Supervisory Board's primary responsibility is to monitor and ensure that all business operations at BMT BEST are conducted in accordance with sharia principles as outlined by the National Sharia Council. Qualitative, descriptive methods were employed for this study. The study's findings led to the conclusion that BMT BEST's Sharia Supervisory Board serves primarily as a meeting venue for outside consultants who advise on matters pertaining to the regulation of financial institutions. Policy guidance for BMT BEST's initiatives was contributed by DPS. Because it is simpler to put into reality than other products with similar characteristics, murabaha finance has seen a surge in popularity in recent years. This money can be used for any number of things, including making purchases, investments, etc. To fulfill its duty to safeguard its members against usury transactions on murabahah financing products, BMT works to verify that contracts for murabahah financing implemented at BMT BEST adhere to sharia regulations. To prevent usury transactions, sharia-compliant contracts for murabahah finance are implemented.